2010
DOI: 10.1177/0218492310387852
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular Nodal Reentrant Tachycardia Treatment Using Novel Potential

Abstract: Radiofrequency ablation of atrioventricular nodal reentrant tachycardia is commonly guided by slow and sharp bipolar potentials of the atrioventricular slow nodal pathway. We optimized the morphology of the guiding potential by unipolar mapping of the slow nodal pathway. We identified a novel unipolar dual-component atrial electrogram at the anterior limb of the coronary sinus ostium. The first component was a positive delta-wave type that corresponded to the isoelectric phase on a bipolar electrogram. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Typical jump, contrary to no jump or multiple jumps, was such an independent variable (8). Our results showed that patients with SP modification were younger, had faster AVNRT, more often received isoproterenol after ablation, and had a higher number of applications as well as procedural time (1,7). These findings may in part be due to the fact that all operators aimed at SP ablation rather than only modification (higher number of applications and procedural duration); however, it is also possible that in patients in whom SP modification was only achieved, AVNRT characteristics were different from those in patients with complete SP elimination.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Typical jump, contrary to no jump or multiple jumps, was such an independent variable (8). Our results showed that patients with SP modification were younger, had faster AVNRT, more often received isoproterenol after ablation, and had a higher number of applications as well as procedural time (1,7). These findings may in part be due to the fact that all operators aimed at SP ablation rather than only modification (higher number of applications and procedural duration); however, it is also possible that in patients in whom SP modification was only achieved, AVNRT characteristics were different from those in patients with complete SP elimination.…”
Section: Discussionmentioning
confidence: 75%
“…safe, data on long-term effects and predictors for success or failure ablation are incomplete. Such issues as SP ablation vs. modification or the use of isoproterenol have been addressed recently by a few studies but results are not concordant [7]. Therefore, the aim of this study was to assess and identification of a predictor for successful AVNRT ablation.…”
Section: Ah Jump As Predictor For Successful Ablation Of Atrioventric...mentioning
confidence: 99%